Mental Emosional Pasien Covid-19 di Rumah Isolasi - Rini Mustikasari Kurnia Pratama; Diane Marlin; Silvia Mariana (Jurnal Ilmiah Universitas Batanghari Jambi, 2022)
Covid-19 is non-natural disaster that has an impact on the wider community. This has a physical and psychological impact on every individual, community who has to undergo isolation or especially because of the Covid-19 condition. One of the effect of psychological impact is mental emotional disorders. The problem of emotional disturbance experienced by patients does not only come from the individual but from the surrounding environment where the condition can worsen if it not handled properly and immediately. The study was conducted in July-September 2021. The sampling technique used total sampling for the variable of mental emotional disorders with conclusion and exclusion criteria. The number of samples is 50 Covid-19 patients in isolation homes. In the variable of emotional mental disorders experienced by Covid-19 patients using the Self Reporting Questionnaire-29 (SQR-29) instrument with the most complaints being complaints of feeling tired easily as many as 39 respondents (78%), followed by compliants of frequent headaches as many as 35 respondents (70%) and did not sleep well 35 respondents (70%). The results of the research obstained are expected to be something that is faced in dealing with Covid-19 patients at home with mental and emotional conflict faced.